Higher prevalence of viral control in HIV-1-infected women in serodiscordant relationships - Peebles, Kathryn (PLoS One, 2018)
BACKGROUND: HIV-1-discordant couples that remain discordant despite repeated exposure may differ from the general population in their distribution of transmission risk factors, including low plasma viral load (PVL) in the infected partner even in the absence of antiretroviral therapy (ART). METHODS: We followed two cohorts of HIV-1-infected Kenyan women: females in discordant couples (FDC) and female sex workers (FSW). We compared the distribution of undetectable (<150 copies/mL) and low PVL (<1,000 copies/mL) between the cohorts using bootstrap methods and exact Poisson regression. RESULTS: We evaluated 296 FDC and 220 FSW. At baseline, FDC were more likely to have undetectable (RR = 6.94, bootstrap 95% CI: 3.47, 20.81) and low PVL (RR = 3.53, bootstrap 95% CI: 2.57, 5.65) than FSW. Similarly, both repeat undetectable PVL (RR = 9.36, bootstrap 95% CI: 6.04, 10.97) and repeat low (RR = 4.99, bootstrap 95% CI: 2.33, 14.04) PVL were more likely among FDC than FSW during follow-up. DISCUSSION: We observed higher prevalence of viral control in FDC compared to FSW in the absence of ART, suggesting potentially higher prevalence of biological HIV resistance factors among discordant couples.